Этноконфессиональные процессы в Закавказье XVII-XVIII вв. - Чобанян, Павел («Զանգակ - 97»)
Düring the ХУП-ХУШ centuries the ethno-confessional processes were extremely active in Armenian-populated areas of the Ottoman Empire and Sefevid Iran. The internse intrusion of Islam and Catholicism be mentioned, which lead to ethnic changes among Armenians and Georgians. As a result, in certain areas of Armenia and Georgia the Turkish language was becoming dominant. But, at the same time, this assimilated population had preserved its national-cultural peculiarities, serving as a link between Muslim and Christian cultures.
Keywords: Этнография